Implementation of character education for vocational high school internship students at Subandi Giyanto Studio - Lestari, Anggita Mundhi; Astuti, Eni Puji (Universitas Negeri Yogyakarta, 2024)
The research aims to describe character education through internships at Subandi Giyanto Studio for vocational students. Character education is implemented through habituation and exemplary. This research uses qualitative research with a descriptive case study method